Development of a VR simulator prototype for myocardial infarction treatment training (2021)
A medical virtual reality simulator provides a learning and practicing tool where trainees are exposed to diverse medical conditions including, the treatment of high-risk pathologies like the myocardial infarction, to develop cognitive and psychomotor skills. Additionally, simulators provide controllable patient conditions that can be configured to improve decision-making in time-sensitive medical procedures. The study of myocardial infarction treatment cardiology relies on analyzing medical cases and patient examination under medical supervision. However, the lack of practice can result in a human error that can be minimized with the simulation. In this paper, a virtual reality simulator prototype that allows students to practice the myocardial infarction procedure based on the American Heart Association guidelines is presented. The proposed prototype uses immersive virtual reality technology to create an engaging situation where the students will be able to recreate the treatment on a virtual patient. The prototype presents an immersive and interactive approach that can benefit the adherence to current myocardial infarction guidelines.